Biological synthesis of silver nanoparticles using β-1, 3 glucan binding protein and their antibacterial, antibiofilm and cytotoxic potential. (February 2018) - Anjugam, Mahalingam; Vaseeharan, Baskaralingam; Iswarya, Arokiadhas; Divya, Mani; Prabhu, Narayanan Marimuthu; Sankaranarayanan, Krishnasamy
Abstract: The present study reports the biological synthesis of silver nanoparticles using crustacean immune molecule β-1, 3 glucan binding protein (β-GBP) purified from the haemolymph of blue swimmer crab Portunus pelagicus . The characterization of synthesized β-GBP based silver nanoparticles ( Pp β-GBP-AgNPs) was made by UV-Vis spectroscopy, XRD, FTIR and TEM analysis. UV-Vis spectra recorded the strong absorbance peak at 420 nm due to its surface plasmon resonance. The XRD analysis revealed the crystalline nature of synthesized nanoparticles with Bragg's reflection peaks at (111), (200), (220), (311) planes. FTIR analysis showed the possible functional groups at 3422, 2926, 2847, 1648, 1556, 1407, 1016 and 669 cm −1 . The mean particle size of Pp β-GBP-AgNPs was 33–47 nm revealed by TEM analysis. Pp β-GBP-AgNPs exhibit appreciable antibacterial activity against Enterococcus faecalis and Pseudomonas aeruginosa when compared to chemical based AgNPs (Chem-AgNPs). The antibiofilm property of Pp β-GBP-AgNPs was assessed through light microscopy and confocal laser scanning microscopy analysis (CLSM), which clearly demonstrates, thickness of E. faecalis and P. aeruginosa preformed biofilm was reduced to 11 μm & 8 μm from 47 μm & 45 μm respectively. Moreover, exopolysaccharide (EPS) quantification and cell surface hydrophobicity (CSH) index exhibited that, Pp β-GBP-AgNPs had the potential to disturb structural integrity of biofilm by upset EPS matrix and bacterial adhesion to hydrocarbons. In addition, the cytotoxic effect of Pp β-GBP-AgNPs was evaluated against human cervical cancer cells (HeLa). Pp β-GBP-AgNPs effectively inhibit the viability of HeLa cells at 50 μg/ml concentration and the morphological changes in Pp β-GBP-AgNPs treated HeLa cells were observed under phase contrast microscopy. Graphical abstract: Image 1 Highlights: β-GBP based silver nanoparticles were synthesized and characterized through UV, XRD, FTIR and TEM analysis. The antibacterial and antibiofilm potential of Pp β-GBP-AgNPs was evaluated and compared with chemical based AgNPs. Cytotoxicity of Pp β- GBP-AgNPs was proved through MTT assay on human cervical cancer cells (HeLa cells).